DTBP‐Mediated Cascade Spirocyclization and Dearomatization of Biaryl Ynones: Facile Access to Spiro[5.5]trienones through C(sp3)−H Bond Functionalization. Issue 31 (17th August 2021) - Zhang, Ming‐Ming; Shen, Liu‐Yu; Dong, Sa; Li, Bing; Meng, Fei; Si, Wei‐Jie; Yang, Wen‐Chao
Abstract: Oxidative radical cascade spirocyclization and dearomatization of biary ynones with a variety of hydrocarbons including toluenes, ethers, ketones, and alkanes has been developed to construct alkyl substituted spiro[5.5]trienones. Abstract : A novel DTBP‐promoted metal‐free cascade cyclization of biary ynones with a variety of hydrocarbons including toluenes, ethers, ketones and alkanes has been established, which provides an expeditious approach to access functionalized spiro[5.5]trienones in moderate to good yields. The products thus obtained represent key structural motifs of biologically active molecules in pesticide.